FINANCIAL ON THE BASIC OF INTERNATIONAL FINANCIAL REPORTING STANDARDS PROCEDURE FOR DRAWING UP REPORTS - Muxidinov Ayubbek Nuritdinovich (American Journals Publishing, 2023)
This article provides a practical analysis of the practical application of international financial reporting standards in Uzbekistan and the problems in the transition to international financial reporting standards and ways to overcome them.
Keywords: International financial reporting, financial accounting and reporting, international financial reporting standards.